Media coverage of mental illness: a comparison of citizen journalism vs. professional journalism portrayals. (3rd September 2019) - Carmichael, Victoria; Adamson, Gavin; Sitter, Kathleen C.; Whitley, Rob
Abstract: Background: Evidence suggests that mainstream media coverage of mental illness tends to focus on factors such as crime and violence. Thus, mental health advocates have argued that alternative portrayals are necessary to reduce stigma. Aim: The aim of this paper is to compare the tone and content of mainstream TV coverage of mental illness with educational videos produced by citizen journalists with mental illness. Methods: We trained three groups of people with mental illness in citizen journalism and participatory video. These groups then produced a series of educational videos about mental illness ( n = 26). Simultaneously, we systematically collected TV clips about mental illness from a major Canadian TV station ( n = 26). We then compared the tone and content of citizen journalism videos vs. TV clips using content analysis techniques. Results: The citizen journalist videos tended to be more positive and hopeful. For example, over 60% of the citizen journalism videos focused on recovery, compared to 27% of the TV clips. Conversely, over 40% of the TV clips focused on crime, violence or legal issues, in comparison to only 23% of the citizen journalism videos. Conclusion: Citizen journalism by people with mental illness has the potential to educate the public and reduce stigma.